Risk Management Analysis of Public Health Facilities as an Effort to Improve Service Units at Community Health Center X - Rizki Khairani Hasibuan; Aradea Margareta; Aulia Biea Belia; Fesya Diva Annisa; Melliani Septiawati; Ahmad Setiawan Nuraya (Journal La Medihealtico, 2026)
Risk management is an essential component in maintaining service quality and patient safety within primary healthcare facilities. This study aims to analyze the implementation of risk management at Puskesmas X Jakarta in 2025, referring to Jakarta Provincial Regulation No. 122 of 2020. The methods used include a literature review, field observations, and questionnaires administered to 76 respondents. The findings indicate that Puskesmas X identified 91 risks, all of which remain within the categories of the 82 risk indicators established by the Ministry of Health, demonstrating a comprehensive identification process. Six risks were designated as priority due to their potential impact on service quality and patient safety. Mitigation efforts, such as relocating the TB room, reorganizing maternity care areas, and conducting patient safety training, were shown to reduce risk levels. The questionnaire results revealed high visitor satisfaction, while the management of medical and liquid waste complied with existing standards. Overall, the implementation of risk management was found to be effective, although further improvements in facility layout, human resources, and risk-based budgeting are needed to support continuous service quality enhancement.